Transformative Learning for Social Justice: Insights From a Blended Seminar - Placida V Gallegos; Steven A. Schapiro (Adult Education Research Conference, 2008)
This paper identifies phases of change and key process factors in a blended graduate seminar on structural inequality and diversity, integrating theory with personal reflection and practice.
Keywords: transformative learning; social justice education; on-line learning.